Desain dan Pengembangan Mesin Press Biobriket Menggunakan Elektro-Pneumatik Sistem berbasis PLC - Razi, Muhammad; Turmizi, Turmizi; Syukran, Syukran; Zulkifli, Zulkifli (Jurnal Mekanova : Mekanikal, Inovasi dan Teknologi, 2024)
This article describes the design and development of a biobriquetting press machine using an electro pneumatic system as the main drive for the process of pressing briquettes, filling raw materials and the process of removing briquettes from the molding cylinder. This machine consists of three pneumatic cylinders, each of which functions as a pressing shaft and ejects briquettes from the cylinder (Ram), inserts and ejects the filling cylinder(feeder) and the mold retaining plate(die) from under the briquette processing frame, and three pressure control valves and direction control valves, pressure control valves and direction control valves controlled by logic programmed in the PLC ladder program. Ladder logic is developed in the PLC to regulate the actuation of DCVs. DCVs make the briquette press machine work fully automatically without any manual intervention so that it will increase the accuracy and efficiency of the press machine. This research aims to produce a biobriquette production machine that works automatically with multi-cycle production, pressure that can be varied, and is able to produce biobriquettes with high capacity and quality.  The system settings of the back-and-forth motion of the molding cylinder, the pressing shaft and the mold retaining plate are controlled by the ladder program in the PLC. This machine uses 3 units of double acting cylinders with a pressure of 10 bar each to press biobriquettes, remove and insert mold cylinders and dies into the processing area. The results showed that the press machine works effectively with multiple production cycles. In one production cycle this machine is capable of producing 40 briquettes in 12 minutes.